European Structural Funds 2014 – 2020 programmes : a public consultation seeking views on the proposals for the implementation of the 2014–2020 European Structural Funds.: a public consultation seeking views on the proposals for the implementation of the 2014–2020 European Structural Funds. (2013) - Scotland., Scottish Government,
No abstract available